Analisis Public Relations PT Telkom Indonesia dalam Meningkatkan Brand Awareness Indihome di Pakulonan - Mustaqim, Mustaqim; Anwar, Muhammad; Santosa, Randi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the strategies and challenges faced by the Public Relations of PT Telkom Indonesia in enhancing Indihome's brand awareness in the Pakulonan area. Using a qualitative approach with in-depth interviews conducted with the marketing communication manager and employees, the study found that the main strategies included the utilization of social media, community event organization, and collaboration with local influencers. These strategies proved effective in broadening audience reach and fostering positive relationships with the community. However, challenges such as infrastructure limitations, price competition, and the public's lack of understanding of fiber-optic technology hindered the efforts' effectiveness. To address these issues, the company needs to accelerate infrastructure development, improve internal communication, and enhance public education. The findings provide critical insights into optimizing communication strategies to support brand awareness growth in the telecommunications industry.